2005
DOI: 10.1097/01.ta.0000197853.49084.3c
|View full text |Cite
|
Sign up to set email alerts
|

The United States Twenty-Year Experience With Bombing Incidents: Implications for Terrorism Preparedness and Medical Response

Abstract: Illegal bombings and related injuries commonly occur in the United States. Because of the easy availability of bombing materials, government agencies and healthcare providers should prepare for potential mass-casualty bombings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Seventy percent of disasters causing >20 dead at the scene are secondary to explosions and fires from a variety of causes, and a 20-year retrospective analysis of bombing events by Kapur et al identified 36,110 bombing incidents, 5931 bomb-related injuries, and 699 bomb-related deaths in the United States during the study period between 1983 and 2002 (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Seventy percent of disasters causing >20 dead at the scene are secondary to explosions and fires from a variety of causes, and a 20-year retrospective analysis of bombing events by Kapur et al identified 36,110 bombing incidents, 5931 bomb-related injuries, and 699 bomb-related deaths in the United States during the study period between 1983 and 2002 (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the last decade of the twentieth century, nearly five illegal bombing attacks occurred each day in the United States [2] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Between 1983 and 2002, 36,110 illegal bombing incidents occurred in the United States [7]. During this same period, there have been only two biologic terrorism incidents in the United States, and, fortunately, there have been no chemical or nuclear events [7].…”
Section: Discussionmentioning
confidence: 99%
“…United States than overseas [7]. Nonetheless, most American health care providers continue to consider terrorism and bombings an international rather than a domestic problem, and few have experience caring for victims of a true mass-casualty event.…”
mentioning
confidence: 92%